Coexistencia de Lutjanus peru y Lutjanus guttatus (Pisces: Lutjanidae) en la costa de Guerrero, México: relación con la variación temporal en el reclutamiento - Chiappa-Carrara, Xavier (2004)
Monthly volumes of capture of Lutjanus peru and Lutjanus guttatus from the coast of Guerrero, Mexico, were analyzed considering eight annual cycles. Time-series, auto correlation, and cross-correlation analysis showed that monthly abundance of populations display unsystematic variations. The FiSAT software was used to obtain the recruitment patterns of both species, using length-frequency data. Our results support the hypothesis that temporal phase-shifts in reproductive events, hence recruitment, explain the coexistence of these species. The outcome of this mechanism is a temporal succession of specific recruit abundance off the coasts of Guerrero, Mexico. The uncoupling of the recruitment events between these species, induces a separation of recruits; therefore, the intake of a particular set of preys could take place at different times.